Sleep Apnea Syndrome and Cognition - Sforza, Emilia (Frontiers in Neurology, 2012)
Obstructive sleep apnea (OSA) is a sleep-related breathing disorder characterized by repetitive episodes of airflow cessation resulting in brief arousals and intermittent hypoxemia. Several studies have documented significant daytime cognitive and behavioral dysfunction that seems to extend beyond that associated with simple sleepiness and that persists in some patients after therapeutic intervention. A still unanswered question is whether cognitive symptoms in OSA are primarily a consequence of sleep fragmentation and hypoxemia, or whether they coexist independently from OSA. Moreover, very little is known about OSA effects on cognitive performances in the elderly in whom an increased prevalence of OSA is present. In this review we will consider recent reports in the association between sleep apnea and cognition, with specific interest in elderly subjects, in whom sleep disturbances and age-related cognitive decline naturally occur. This will allow us to elucidate the behavioral and cognitive functions in OSA patients and to gain insight into age differences in the cognitive impairment. Clinically, these outcomes will aid clinicians in the evaluation of diurnal consequences of OSA and the need to propose early treatment.